KESULITAN ANAK BERKEBUTUHAN KHUSUS TUNAGRAHITA DALAM MENYELESAIKAN OPERASI BILANGAN DENGAN PEMBERIAN SCAFFOLDING BERBANTUAN PUZZLE: Kesulitan Anak Berkebutuhan Khusus Tunagrahita Dalam Menyelesaikan Operasi Bilangan Dengan Pemberian Scaffolding Berbantuan Puzzle - Lailah, Azza Nur; Ni'matul Mahbubah; Ulfa Masamah (Journal of Mathematics Learning Innovation, 2026)
Children with intellectual disabilities often have difficulty understanding numerical concepts and performing arithmetic operations, which remains a common problem in mathematics education in special schools. This study aims to describe these difficulties and the changes in children's abilities after being given puzzle-assisted scaffolding. The study used a qualitative approach with a Single Subject Research (A–B–A) design, which included an initial baseline phase (A1), an intervention phase (B), and a second baseline phase (A2). The research subject was a child with moderate intellectual disability who still experienced difficulties in recognizing numbers and completing simple arithmetic operations. Data were collected through observation, interviews, and documentation, then analyzed qualitatively through data reduction, data presentation, and conclusion drawing. The results showed that in phase A1, the child experienced difficulties in recognizing two-digit numbers, understanding operation symbols, and calculating independently. In phase B, scaffolding and puzzles helped improve children's understanding and accuracy in completing number operations. In phase A2, some of the acquired skills remained even without assistance, although they were not yet fully stable. This study concluded that puzzle-assisted scaffolding had a positive impact on the understanding of number operations in children with intellectual disabilities, but continuous practice was still needed to achieve consistency in skills.